Pengembangan Game Visual Novel Sebagai Media Pembelajaran Bahasa Inggris Menggunakan Metode ADDIE - Geofany Galindra; Fahrobby Adnan; Januar Adi Putra (Faculty of Computer Science, University of Jember, 2023)
The methods and media that are used in the teaching and learning process are crucial to its success. With the use of suitable learning resources, teachers and students can overcome barriers to learning, enabling students to quickly access and comprehend course material. The survey was conducted in SD Negeri 1 Rogojampi, and the findings revealed that teachers only verbally communicated knowledge to the students while they were learning. With the use of an Android-based Visual Novel Game and the ADDIE method, the researcher hoped to innovate in the development of English learning media. Sixth-grade elementary school students who were randomly selected as respondents during the implementation stage were divided into groups that used learning media and groups that did not. According to the expert validation results, learning media are practicable to use and test on respondents. There were no problems in the learning media during the small group test, allowing it to be continued to the implementation stage or the big group test on research respondents. The respondents are put into two groups for comparison purposes: the group that received learning media and the group that did not. The average comparison value between the groups using learning media and the groups not using learning media differs by 2.9, showing that visual novel learning media is both useful and effective as a learning medium.